Evaluation of an International Entrepreneur Exchange Program: Impacts, Lessons Learned, and Implications for Agricultural Development - K. S. U. Jayaratne; Lisa K. Taylor; Craig M. Edwards; Shelly Sitton; Dwayne D. Cartmell II; Craig E. Watters; Shida R. Henneberry (Journal of International Agricultural and Extension Education, 2017)
This study evaluated a two-way, visitor exchange project for entrepreneurship development between three African countries and the United States. The study’s purpose was to determine outcomes, understand lessons learned, and derive implications for international agricultural development. Findings of the study confirm visiting African Entrepreneur Fellows (AEFs) developed entrepreneurial knowledge, gained business skills, and acquired positive attitudes toward U.S. business and culture. The majority of AEFs had applied acquired knowledge and skills to improve their businesses and promoted open economic ideals, business ethics, and human rights in their businesses. As a result, AEFs were able to expand their business into new ventures, improve customer services, establish communication networks, and serve their communities. Visitor exchange, entrepreneurship-building programs are effective strategies in contributing to development efforts in developing countries. Paying due attention to the selection and matching of U.S. mentors with the business interests and learning needs of international fellows is necessary to ensure their learning expectations are met. It is important to assign international participants with suitable mentors for longer periods of time to increase the likelihood of receiving more in-depth learning experiences and develop lasting professional relationships to further collaboration. Realization of the potential of entrepreneurship-focused, visitor exchange programs between nations as a strategy for international agricultural development is the major implication of this study.
Keywords: entrepreneurship development; Sub-Saharan Africa; visitor exchange programs